HUBUNGAN DUKUNGAN KELUARGA DENGAN TINGKAT KECEMASAN PADA ANAK USIA PRASEKOLAH YANG DI HOSPITALISASI DI RS SYECKH YUSUF GOWA - haikal alpin (Stikes Graha Edukasi Makassar, 2019)
ABSTRACTObjective: To know the relationship of family support with anxiety level in children who were hospitalized pre-school age in Syech Yusuf Gowa Hospital in 2016. Method: In this study, the research design used was analytical with cross sectional approach, the sample was taken using purposive sampling, data analysis through computer program with error rate 0,05. The number of samples in this study were 30 respondents and using questionnaires and interview sheets. Chi-Square test was conducted to assess the relationship between independent variables (family support) and dependent variable (anxiety). Results: The chi-square test shows that there is a relationship of family support with anxiety level in preschool age children with p = 0,017 (p <0,05). Discussion: Family support is the attitude, action, appreciation, encouragement, and spirit given by the family to the child being hospitalized. Anxiety is a person's emotional upheaval associated with something outside of himself and the mechanisms of self used in overcoming problems. Conclusion: good family support relationships can affect anxious response to children especially in hospitalization process